POTENTIAL BREEDING SITES AND ORGANOPHOSPHATE RESISTANCE STATUS OF AEDES SPP. IN YOGYAKARTA - Nila Qudsiyati; Fitri Ainun Nazara; Jeremy Tertius Kilima; Soenarwan Hery Poerwanto (Universitas Airlangga, 2022)
Background: The discovery of Aedes spp. in the breeding sites is the leading cause of the high incidence of Dengue Hemorrhagic Fever (DHF) in Yogyakarta in 2019. This incidence can be calculated based on the Container Index (CI), House Index (HI), and Breteau Index (BI). Efforts to control the density of Aedes spp. The use of organophosphate insecticides in the long term and with the wrong dose will cause resistance. Purpose: This research was conducted to determine the potential breeding sites, the density, and the organophosphate resistance status of Aedes spp. in Yogyakarta. Methods: A literature review with the criteria of referenced journals from 2011-2020, national journals accredited at least Sinta 5 to Sinta 1 and international journals at least Q4 to Q1. Results: This study shows that the potential breeding sites for Aedes spp. in Yogyakarta, in general, are both indoors or outdoors, stagnant clean water, opened, not exposed to direct sunlight, and the duration of not eradicating the mosquito nests > 1 month. Aedes spp. in Yogyakarta has a high population density, so it is at high risk of transmitting dengue cases. The resistance status of Aedes spp. in various regions of Yogyakarta are categorized as resistant to organophosphate insecticides. Conclusion: Literature review requires field research also, implementation of prevention through the mosquito nests eradication program and 3M (Shutting, Draining, and Burying), and the replacement of insecticides types other than organophosphates.